Harmonizing the Neurobiology and Treatment of Obsessive-Compulsive Disorder - Goodman, Wayne K. (Am J Psychiatry, 2021)
Obsessive-compulsive disorder (OCD) is a common, chronic, and oftentimes disabling disorder. The only established first-line treatments for OCD are exposure and response prevention, and serotonin reuptake inhibitor medications (SRIs). However, a subset of patients fails to respond to either modality, and few experience complete remission. Beyond SRI monotherapy, antipsychotic augmentation is the only medication approach for OCD with substantial empirical support. Our incomplete understanding of the neurobiology of OCD has hampered efforts to develop new treatments or enhance extant interventions. This review focuses on several promising areas of research that may help elucidate the pathophysiology of OCD and advance treatment. Multiple studies support a significant genetic contribution to OCD, but pinpointing the specific genetic determinants requires additional investigation. The preferential efficacy of SRIs in OCD has neither led to discovery of serotonergic abnormalities in OCD nor to development of new serotonergic medications for OCD. Several lines of preclinical and clinical evidence suggest dysfunction of the glutamatergic system in OCD, prompting testing of several promising glutamate modulating agents. Functional imaging studies in OCD show consistent evidence for increased activity in brain regions that form a cortico-striato-thalamo-cortical (CSTC) loop. Neuromodulation treatments with either noninvasive devices (e.g., transcranial magnetic stimulation) or invasive procedures (e.g., deep brain stimulation) provide further support for the CSTC model of OCD. A common substrate for various interventions (whether drug, behavioral, or device) may be modulation (at different nodes or connections) of the CSTC circuit that mediates the symptoms of OCD.